1998
DOI: 10.1002/(sici)1097-4652(199810)177:1<76::aid-jcp8>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin receptor expression and responsiveness of human monocytic cells to thrombin is linked to interferon‐induced cellular differentiation

Abstract: Human thrombin has been shown to stimulate monocyte chemotaxis, phagocytosis, and interleukin (IL8) production, but the mechanisms responsible for stimulation are not well defined. In some cells, thrombin stimulation of proliferation appears to require both cleavage of the proteolytically activated receptor for thrombin (PAR1) and activation of a nonproteolytically activated thrombin receptor (N-PAR), while in others activation of either receptor alone may be sufficient for stimulation. We, therefore, have ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Last, only the low‐flow and high‐flow circuits documented a log‐fold increase in a proinflammatory cytokine. Tumor necrosis factor alpha, a specific marker of monocyte activation, is associated with a significant increase in thrombogenicity . The combined generation of procoagulant and proinflammatory stimuli likely contribute to ECMO‐related morbidity and offer targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Last, only the low‐flow and high‐flow circuits documented a log‐fold increase in a proinflammatory cytokine. Tumor necrosis factor alpha, a specific marker of monocyte activation, is associated with a significant increase in thrombogenicity . The combined generation of procoagulant and proinflammatory stimuli likely contribute to ECMO‐related morbidity and offer targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that thrombin elicits proinflammatory activities by activation of PAR‐1 receptor ( Cirino et al , 2000 ; Vergnolle et al , 2001 ). In previous studies, we showed that PAR‐1 expression and responsiveness of cells to thrombin were linked to IFN γ ‐induced differentiation ( Naldini et al , 1998 ). Other laboratories have also shown that leukocytes express PAR‐1 ( Howells et al , 1993 ) and that PARs are associated with inflammation ( Cirino et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PAR 1 ‐ and PAR 2 ‐APs, but not PAR 3 ‐ or PAR 4 ‐APs, induced IL‐6, but not IL‐13, release from cultured human T cells (Li and He, 2006). PAR 1 activators have also been reported to induce CCL2, IL‐1β and TNF‐α release from macrophages (Naldini et al. , 1998; 2002; Riewald et al.…”
Section: Par‐mediated Effects In the Lungmentioning
confidence: 99%